Characterization of the Runx gene family in a jawless vertebrate, the Japanese lamprey (Lethenteron japonicum). - Giselle Sek Suan Nah; Boon-Hui Tay; Sydney Brenner; Motomi Osato; Byrappa Venkatesh (PLoS ONE, 2014)
The cyclostomes (jawless vertebrates), comprising lampreys and hagfishes, are the sister group of jawed vertebrates (gnathostomes) and are hence an important group for the study of vertebrate evolution. In mammals, three Runx genes, Runx1, Runx2 and Runx3, encode transcription factors that are essential for cell proliferation and differentiation in major developmental pathways such as haematopoiesis, skeletogenesis and neurogenesis and are frequently associated with diseases. We describe here the characterization of Runx gene family members from a cyclostome, the Japanese lamprey (Lethenteron japonicum). The Japanese lamprey contains three Runx genes, RunxA, RunxB, and RunxC. However, phylogenetic and synteny analyses suggest that they are not one-to-one orthologs of gnathostome Runx1, Runx2 and Runx3. The major protein domains and motifs found in gnathostome Runx proteins are highly conserved in the lamprey Runx proteins. Although all gnathostome Runx genes each contain two alternative promoters, P1 (distal) and P2 (proximal), only lamprey RunxB possesses the alternative promoters; lamprey RunxA and RunxC contain only P2 and P1 promoter, respectively. Furthermore, the three lamprey Runx genes give rise to fewer alternative isoforms than the three gnathostome Runx genes. The promoters of the lamprey Runx genes lack the tandem Runx-binding motifs that are highly conserved among the P1 promoters of gnathostome Runx1, Runx2 and Runx3 genes; instead these promoters contain dispersed single Runx-binding motifs. The 3'UTR of lamprey RunxB contains binding sites for miR-27 and miR-130b/301ab, which are conserved in mammalian Runx1 and Runx3, respectively. Overall, the Runx genes in lamprey seem to have experienced a different evolutionary trajectory from that of gnathostome Runx genes which are highly conserved all the way from cartilaginous fishes to mammals.